Antimicrobial Activity of Polyhexamethylene Guanidine Derivatives Introduced into Polycaprolactone - Brzezinska, Maria Swiontek; Walczak, Maciej; Jankiewicz, Urszula; Pejchalová, Marcela (Springer, 2018)
The research was aimed at determining the abundance of biofilm formation by Escherichia coli and Staphylococcus aureus on the surface of polycaprolactone (PCL) with polyhexamethylene guanidine (PHMG) derivatives and effect of the derivatives on extracellular hydrolytic enzymes and intracellular dehydrogenases. Biofilm abundance was determined by spectrophotometry, using crystal violet staining. Hydrolytic enzymes after contact with the film were determined with the use of non-specific substrate-fluorscein diacetate. The effect of PHMG derivatives on dehydrogenases activity was assessed using the test, where triphenyltetrazolium chloride (TTC) is reduced to triphenylformazan (TF). The PCL containing PHMG granular polyethylene wax and salt of sulfanilic acid (0.6-1% wt.) strongest inhibited biofilm formation. PHMG derivatives introduced into PCL were found to slightly affect hydrolases activity in both E. coli and S. aureus at a concentration of 0.2 and 0.6%. It was also found that dehydrogenases activity was inhibited by PCL films containing PHMG derivatives. PCL containing 1% of PHMG sulfanilate strongest inhibited hydrolases activity, whereas PCL modified with 1% of PHMG granular polyethylene wax showed the highest inhibitory effect on the activity of both enzymes. W-PCL and A-PCL composites (at concentration of 0.6%) have optimal combination of antibiofilm activity and biodegradability.
Antimikrobiální účinnost derivátů polyhexamethylenguanidinu inkorporovaných do polykaprolaktonu
Keywords: Polycaprolactone; PHMG derivatives; Hydrolases; Dehydrogenases; Polykaprolaktony; hydrolázová aktivita; dehydrogenázová aktivita